Adherence to combined healthy lifestyle and odds of metabolic syndrome in Iranian adults: the PERSIAN Dena cohort study - Mohammad-Reza Jowshan; Abdollah Pourjavid; Farshad Amirkhizi; Mohammad-Hossein Hosseini; Mohammad-Amin Zolghadrpour; Soudabeh Hamedi-Shahraki; Amin Hossaini Motlagh; Somayyeh Asghari (Scientific Reports)
Abstract The relationship between lifestyle choices and health outcomes has received significant scholarly attention. Research indicates that factors such as obesity, insufficient physical activity, tobacco use, and poor dietary habits may elevate the odds of developing metabolic disorders. This study aimed to investigate the association between the combined healthy lifestyle score (HLS) and the odds of metabolic syndrome (MetS) and its associated components in a population of apparently healthy adults. This cross-sectional study utilized data from the Dena PERSIAN cohort, which comprised 2,971 healthy adults. Participants’ combined HLS were evaluated using validated questionnaires that assessed body mass index (BMI), physical activity level (PAL), smoking status, and dietary quality. The evaluation of dietary nutritional quality was conducted using the most recent version of the Healthy Eating Index (HEI), known as HEI-2020. The combined HLS was measured on a scale ranging from zero, indicating an unhealthy lifestyle, to four, representing the healthiest lifestyle. Individuals with the highest combined HLS score had 81% lower odds of having MetS compared to those with the lowest score (OR: 0.19; 95% CI: 0.11–0.33). Higher combined HLS scores were significantly associated with decreased odds of abdominal adiposity (OR: 0.11; 95% CI: 0.07–0.18), abnormal glucose homeostasis (OR: 0.55; 95% CI: 0.35–0.86), elevated serum triglycerides (OR: 0.41; 95% CI: 0.26–0.67), and low high-density lipoprotein cholesterol (HDL-C) levels (OR: 0.39; 95% CI: 0.24–0.65) after adjusting for sex, age, education level, and marital status (P < 0.05). The findings indicated a significant association between adherence to a combined HLS and a decreased odds of developing MetS and its associated components among Iranian adults.